Politeness Strategies on "Harry Potter and the Half Blood Prince" Movie - Bertaria Sohnata Hutauruk (Journal of English Language and Culture, 2018)
This research deals with the use Positive Politeness in “Harry Potter and the Half Blood Prince” Movie. To do the research, the writer formulates the problem as follow: (1) What Positive Politeness strategies are used in “Harry Potter and The Half Blood Prince” Movie? 2. What is the most dominant strategy of Positive Politeness Used in “Harry Potter and The Half Blood Prince” Movie? This study is focused on Brown and Levinson (1987) positive politeness theory by using fifteen strategies of positive politeness. The objective of the study are to describe and determine the positive politeness used in that movie. The data are obtained from all the dialogues in that movie. This study was conducted by using descriptive qualitative design. The subject of this study is “Harry Potter and the Half-Blood Prince” movie, and the objects are the fifteen strategies of positive politeness. The techniques of collecting data are by watching movie, identifying and transcribing the script of the dialogues then put them into columns. The data is analyzed by identifying and transcribing the script of the dialogues, classifying the positive politeness strategies used in that movie then counting it and find out the dominant positive politeness strategy. The findings of the data analysis show that there are thirteen of fifteen strategies of positive politeness found in the movie each with the number and percentage of occurrences. Politeness strategy is important in our life because it can make harmonious interactions. Keywords:  politeness, strategies, movie